(untitled) (Proceedings of the International Conference on Social Sciences, 2018)
Based on research using in-depth interviews with four women survivors of interpersonal violence from urban India, this study attempts to understand three key aspects of interpersonal violence against women. The first objective is to understand how survivors define and interpret the meaning of the term ‘violence’. The second objective is to locate the question of gender into the study of interpersonal violence in India. The final objective is to analyse how institutions around survivors that are posited as being a refuge for them respond to their experience of violence. The findings of the study point to a dismal reality wherein the aforementioned institutions don’t only prove ineffective in helping the survivor cope with their experience of violence, but also inflict more violence upon them due to the existing norm of patriarchal social culture.